2001
DOI: 10.2135/cropsci2001.4141253x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of QTL for Resistance to White Mold Disease in Common Bean

Abstract: White mold (WM), incited by Sclerotinia sclerotiorum (Lib.) de Bary, is a serious disease of common bean (Phaseolus vulgaris L.). However, plant breeders have had very limited success in developing resistant (R) cultivars. Molecular markers linked to genes for R to WM may improve selection for R. The objective was to identify random amplified polymorphic DNA (RAPD) markers linked to quantitative trait loci (QTL) for partial physiological resistance (PPR), partial field resistance (PFR), porosity over the furro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
107
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 36 publications
10
107
1
Order By: Relevance
“…coccineus populations. In contrast to single inheritance, more than ten quantitative trait loci (QTL) have been identified that influence resistance to white mold, mostly with small to moderate effects (Milkas et al 2001, Park et al 2001, Kolkman and Kelly 2003, Milkas et al 2003, Ender and Kelly 2005. Resistance QTL have been located on all linkage groups (chromosome) except 9, 10 and 11 of the integrated common bean map , Miklas et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…coccineus populations. In contrast to single inheritance, more than ten quantitative trait loci (QTL) have been identified that influence resistance to white mold, mostly with small to moderate effects (Milkas et al 2001, Park et al 2001, Kolkman and Kelly 2003, Milkas et al 2003, Ender and Kelly 2005. Resistance QTL have been located on all linkage groups (chromosome) except 9, 10 and 11 of the integrated common bean map , Miklas et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative trait mapping of resistance to S. sclerotiorum in common 1 bean, sunflower, and rapeseed revealed numerous small-effect QTL (Park et al 2001;Bert et al 2002;Zhao and Meng 2003). Studies of quantitative resistance to B. cinerea in tomato and Arabidopsis found QTL explaining 12-15% (tomato) and 5-10% (Arabidopsis) of phenotypic variance for traits associated with resistance to B. cinerea (Denby et al 2004;Finkers et al 2007).…”
mentioning
confidence: 99%
“…For example, binary data are often found when the aim is to improve traits such as disease status (Setiawan et al, 2000;Park et al, 2001), mortality or survival (Mora et al, 2008d), flowering (Missiaggia et al, 2005;Mora et al, 2007;Mora et al, 2009), among other traits. Yang et al (2009) stated that deviations from this assumption may affect the accuracy of QTL detection and lead to detection of spurious QTLs.…”
Section: Resultsmentioning
confidence: 99%